PENGARUH LINGKUNGAN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN PT SANDIN INDONESIA - ., Yusnaldi; Pujiati, Herni; Faisal, Ahmad (Jurnal Ilmiah Manajemen SURYA PASCA SCIENTIA, 2024)
This study aims to analyze the effect of work environment and work stress on the performance of employees of PT Sandin Indonesia. The sample in this study were 74 respondents. The method used in this study is a quantitative method and data collection is done by distributing questionnaires which are then processed using IBM SPSS 22 analysis tools. The results showed that partially (t) it was found that brand image had a significant effect on customer satisfaction. This is evidenced by the significance value smaller than 5% confidence level (0,000 <0.05) and tcount> t table (2.284> 1.99). Based on the partial test results (t) it was found that customer value has a significant effect on customer satisfaction. This is evidenced by the significance value smaller than 5% confidence level (0.029 <0.05) and tcount> t table (2.234> 1.99). The test results (R2) obtained a value of 0.847 so, brand image and customer value can explain the variable customer satisfaction by 84.7%, while the remaining 15.3% is explained by other variables